Pricing models of covered bonds – a Nordic study - Sulku, Petri; Falkenbach, Heidi (International Journal of Strategic Property Management, 2011)
Covered bonds are an alternative way of investing indirectly in the debt side of real estate, which is beneficial for investors looking for alternatives to government or corporate bonds. Due to the dual nature of the protection offered by covered bonds, they have a justified place in investors' portfolios. This paper studies the pricing of covered bonds and tests it with data gathered from the nordic countries. Using the tested reduced form model, it was possible to price covered bonds with satisfactory results. The estimated model was highly statistically significant and performed according to the economic reasoning behind it. The estimated model also worked well in comparison to research conducted earlier on competing models, such as the structural models.First Publish Online: 4 Jul 2011